Stimulating Problem-Solving Skills in Early Childhood: A Qualitative Thematic Literature Review of Learning Strategies (THUFULA, 2025)
Problem-solving skills are essential 21st-century competencies needed to equip children for navigating an increasingly complex global landscape. However, comprehensive syntheses of effective learning strategies that align with the Indonesian ECE context remain limited in recent research. This study is a qualitative literature review using a synthetic–thematic approach conducted through systematic searches on Google Scholar, ERIC, DOAJ, and ResearchGate, with inclusion criteria covering publications from 2020–2025, relevance to early childhood problem-solving development, and empirical grounding. Twenty-one articles that met the criteria were analyzed using Braun and Clarke’s thematic analysis procedures. The results show that consistently effective strategies include the STEAM approach, project-based learning, simple science experiments, traditional games, and constructive play—all of which promote exploration, causal reasoning, creativity, and collaboration. Key challenges include limited teacher competence, insufficient exploratory facilities, and low levels of family engagement. Theoretically, the findings reinforce the importance of constructivist and sociocultural perspectives in the development of problem-solving skills, while practically, they highlight the urgency of strengthening teacher capacity and designing stimulus-rich learning environments. The novelty of this study lies in its comprehensive integration of multiple pedagogical approaches within a single analytical framework sensitive to the Indonesian context. Overall, this review provides an important conceptual foundation and strategic direction for future research and ECE practices aimed at enhancing problem-solving abilities in young children.